A model for analyzing influence of timber production on lichens for reindeer grazing - Eriksson, Olof; Sandewall, Mats; Wilhelmsson, Erik (Rangifer, 1987)
A model for long-term analysis of the influence of timber production on lichens for reindeer grazing (Cladina, Alectoria, Bryoria spp and others) in Sweden is presented. The annual production of and demand for lichens are estimated and compared. Production of these lichens is presumed to set the upper limit for the reindeer population. Reindeer graze on both ground and tree lichens, which both must be accessible in sufficient amounts and at the right times of the year if reindeer husbandry is to succeed without supplementary feeding. The model is based mainly on existing data, and uses are estimations from the National Forest Survey and the Hugin system for calculation of longterm potential cut (Bengtsson, 1981). Geographically the study is limited to Vasterbotten and Norrbotten, the northernmost counties in Sweden, where most reindeer husbandry in Sweden is located, and where reindeer grazing takes place over almost the whole area. The calculations cover a period of one hundred years from 1980, and are based on a timber production programme which relies more on «multiple use» than the current Swedish forest policy (Bengtsson, 1986). The annual production of ground lichens is calculated by multiplying the area covered with ground lichens by their increment as estimated from their rate of biomass increase, which in turn depends on site factors and age of the stand. The estimation of the area is based on data from the National Forest Survey. Sample plots with ground lichens are assumed to maintain lichens during the whole hundred year period. Areas with stands that have been thinned within ten years and stands younger than 20 years are excluded due to logging residues from thinnings and packed snow. Some of the remaining area cannot practically be utilized for reindeer grazing. Representatives of three communities of reindeer herders classified 212 plots from the National Forest Survey with ground lichens and assessed that 3/4 of the plots can be utilized. The reduction was because of location (near buildings, roads, railroads, and recreation facilities), or because the area with lichens was too small and isolatéd. Demand for ground lichens is calculated as the daily demand for ground lichens by the reindeer multiplied by the number of days every year that reindeer depend on this forage. Figures used are based upon estimations from persons with great experience of reindeer farming. The annual production of tree lichens consists of two parts, i.e., tree lichens within reach of the reindeer, and tree lichens which become accessible after falling down from the trees onto the snow. Forest stands dominated by conifers and older than one hundred years are assumed to bear tree lichens. This area is also reduced to 75 per cent for reasons of practical accessibility. Annual production of lichens in reach of the reindeer is then estimated as the area multiplied by the increment rate of the biomass. One quarter of the annually fallen tree lichens is assumed to be available as fodder during late winter/early spring. The demand for tree lichens is principally estimated in the same way as for ground lichens, but the number of days per years is lower because tree lichens are mainly considered to be fodder in distress periods. Two sources of uncertainty are present in the results, namely the influence of factors not included in the models, and the influence of uncertainty in factors included in the models. The models used to estimate production and demand obviously imply simplifactions of true relations. These simplifications are mainly due to a basic lack of knowledge, one example being that variation, i.e. in volume per hectare, might very well influence the production of lichens, but is not taken into consideration in the models. One example of uncertainty in data used is the increment rate of lichen fodder. Another example is the estimation of biomass of lichens, here based upon investigations (Eriksson, unpubl.) with other purposes than to provide data about grazing availability in the large geographic regions used in this study. The possibilities for drawing reliable conclusions will increase when better estimations of input data and relationship are available. The geographic division into four regions is a result of the design of the National Forest Survey. However, great differences may be present within these geographic areas, each containing a number of communities of reindeer herders. Thus, results are not applicable to single communities of reindeer herders. The study illustrates a method of revealing how lichen fodder for reindeer will develop in relation to timber production. The results of the calculations, however, are too uncertain to allow reliable conclusions to be drawn. Nonetheless, the results indicate that in some areas there is already a shortage of lichen fodder for the number of reindeer assumed in this study. The calculations hint that production will decrease in the future. These indications should motivate more research in this topic. If the results of this study are accurate and if forestry develops according to the assumptions, the owners of the reindeer will have to continue or increase the supplementary feeding and/or reduce the number of reindeer significantly. They will also have to utilize all of the areas that are possible to graze, even if some of them today are considered to be of marginal value for reindeer grazing. Another way to improve the balance of production and demand is to adjust forest management on areas with lichens to a greater extent than has been done in the timber production alternative analysed in this study.Virkesproduktionens inverkan på renskotselns lavbete - En metodstudie.Abstract in Swedish / Sammanfattning: En modell for långsiktig analys av virkesproduktionens inverkan på renskotselns lavbete(Cladina, Alectoria, Bryoria spp mfl) i Sverige presenteras. Modellen beråknar årlig produktion och behov av lavbete, ef^ersom tillgången på dessa lavar bedoms begrånsa renpopulationen. Både tråd- och marklavar betas av renarn£| och måste finnas tillgångliga i tillråcklig mångd och vid rått tidpunkt under året om renskotseln skall klara sig utan stodutfordring. Modellen bygger huvudsakligen på redan existerande data. Skattningarna av areal gors med data från riksskogstaxeringen och från beråkningar med Hugin-systemet for långsiktiga analyser av avverkningsmojlighe-terna (Bengtsson, 1981). Studien begrånsas geografiskt till Norr- och Våsterbottens lån. Beråkningarna gors for en hun^raårsperiod med start 1980, och bygger på ett virkesproduktionsprogram i A VB-85 som syftar till mera mångbruk an dagens skogspolitik (Bengtsson, 1986). Den årliga produktionen av marklav skattas som produkten av mångden marklav per hektar, dess till-våxtprocerit och arealen med marklav. Mångden marklav per hektar beror av ståndortsforhållanden och bes-tåndsåldern. Skattningen av arealen baseras på uppgifter från riksskogstaxeringen. Provytor med marklav antas vara laybårande under hela prognosperioden. Provytor dår beståndsåldern år lågre ån 20 år, samt provytor som i awerkningsberåkningen rojts eller gallrats under senaste tioårsperiod råknas dock bort. Orsaken år att snopacknirig och kvarlåmnade stammar och ris forsvårar eller omojliggor for renen att komma åt laven. Hela den återstående arealen kan dock inte nytt jas for planerad renskotsel. Representanter for tre samebyar bedomd)e 212 av riksskogstaxeringens provytor med marklav med avseende på om de kan nytt jas for planerad renskotsel. Resultatet blev att 3/4 av provytorna ansågs kunna utnyttjas. Provytor råknades bort på grund av belågenlhet nåra byggnader, vågar, jårnvågar och friluftsanlåggningar, eller pga att arealen med marklav var for liten och isolerad for att kunna utnyttjas. Behovet av marklav beråknas som produkten av det genomsnittliga dygnsbehovet for en ren, antalet renar samt det ailital dagar per år som renarna bedoms ha behov av detta foder. De två senare uppgifterna grundas på uppskattningar av personer med stor erfarenhet av renskotsel. Den årliga produktionen av trådlavar består dels av lavtillvåxten i det betningsbara hojdintervallet, dels av trådlav som faller ner på snon. Barrdominerade bestånd aldre ån hundra år antas vara trådlavbårande, men åven denna areal reduceras med hånsyn till praktisk tillgånglighet. Årlig produktion av trådlav inom råckhåll for renen skattas som produkt av mångden trådlav, dess tillvåxtprocent och arealen. Av den trådlav som årli-gen faller n)er på marken antas en fjårdedel vara tillgånglig under vårvintern. Efterfrågan på trådlav beråknas på i princip samma sått som efterfrågan på marklav, men antal betningsda-gar per år åk lågre eftersom trådlav huvudsakligen år ett visserligen hogkvalitativt och låttillgångligt, men dock nodfoder. Resultaten år osåkra av två huvudorsaker. Dels pga inverkan av faktorer som inte ingår i modellen, dels osåkerhetejn i de faktorer som ingår i modellen. Modellen innehåller uppenbart forenklingar av verkliga samband. Dessa forenklingar beror huvudsakligen på viss brist på grunddata. Mojligheterna att dra såkre slutsatser kommer att oka i takt med båttre kunskap om utnyttjade samband och uppgifter. Den geografiska indelningen i lånsdelar beror på utformningen av riksskogstaxeringen. Forhållandena kan givetvis variera inom dessa lånsdelar, som var och en består av ett flertal samebyar. Resultaten får således inte tillåmpas på enskilda samebyar. Studien visar på en metod for att belysa hur renskotselns lavbete kommer att utvecklas i relation till virkes-produktionen. Resultaten år dock allt for osåkra for att man skall kunna dra några såkra slutsatser. Resultaten antyder emellertid att for vissa områden finns redan i dag en brist på lavbete for den renpopulation som kalkylerats med i denna studie. Beråkningarna antyder att produktionen av lavbete kommer att minska i framtiden, vilket bor motivera mer forskning inom området. Om resultaten i denna studie år riktiga och om det virkesproducerande skogsbruket utvecklas enligt exemplet, måste renågarna fortsåtta med eller utoka stodutfodringen och/eller minska antalet renar betydligt. De tvingas också utnyttja alla betningsbara områden, åven sådana som for nårvarande anses vara marginella. Ett annat sått att forbåttra balansen år att modifiera det virkesproducerande skogsbruket på arealer med lavbete i storre utstråckning ån vad som gors i det alternativ som analyseras hår.Puuntuotannon vaikutus jäkälälaitumiin.Abstract in Finnish / Yhteenveto: Artikkelissa esitetåån pitkånaikavålin analyysimalli puuntuotannon vaikutuksista ruotsin jåkålå-laitumille (Cladina, Alectoria, Bryoria spp. ym.). Koska jåkålien saantia pidetåån porojenlukumååråå rajoittava, laskee malli jåkålålaidunten vuotuisen tuoton ja tarpeen. Porot laiduntavat sekå puussa ettå maassa kasvavia jåkåliå, ja nitå molempia on oltava saatavilla, sekå tarvittava måårå, ettå oikeaan aikaan vuodesta, jos poronhoito aikoo selviytyå ilman tukiruokintaa. Malli rakentuu pååsiassa jo aikaisemmin hankittuihin tietoihin. Pinta-ala arviot tehdåån valtakunnanmetsånarvioinnin tietojen, ja hakkuumahdollisuuksien pitkånaikavålin analysoimiseksi perustetun Hugin-systeemin laskelmien avulla (Bengtsson, 1981). Maantieteellisesti tutkielma rajoittuu Norrbotte-nin ja Våsterbottenin lååneihin. Laskelmat tehdåån sadanvuoden aikavålille alkaen 1980, perustuen yhteen AVB-85:en puuntuotantoohjelmaan, joka tåhtåå tåmånpåivåistå laajempaan metsien moninaiskåyttoon (Bengtsson, 1986). Vuotuinen maassa kasvavien jåkålien tuotanto arvioidaan jåkålien hehtaarimåårien, sen kasvuprosentin ja pinta-alan tulona. Jåkålien måårå hehtaaria kohti on riippuvainen kasvupaikan ja metsikon iåstå. Pinta-ala arviot perustuvat valtakunnanmetsånarvioinnin tietoihin. Jåkålåå kasvavien koealojen odotetaan pitåvån jåkå-låkasvustonsa koko prognoosiajan. Koealat, joissa metsikon ikå on alle 20 vuotta, sekå koealat, jotka hak-kuulaskelmissa on perattu tai harvennettu viimeisen kymmenen vuoden aikana, on jåtetty huomioimatta. Syynå tåhån on lumenpakkaantuminen, sekå jåljelle jåtetyt rungot ja oksat, jotka vaikeuttavat tai tekevåt po-rojen jåkålån saannin mahdottomaksi. Vuotuinen puussa kasvavien jåkålien tuotanto koostuu, osittain poron ulottuvilla olevasta, ja osittain lu¬melle putoavasta jakålåstå. Yli sata vuotta vanhojen havupuuvaltaisten metsikkojen oletetaan tuottavan puussa kasvavia jåkåliå, mutta myos tåmå pinta-ala pienenee kåytånnon syistå. Vuotuinen poronulottuvilla puussa kasvavien jåkåliå tuotanto arvioidaan jåkålån måårån, sen kasvuprosentin ja pinta-alan tulona. Yksi neljånnesosa siitå vuosittain lumelle tippuvasta jåkålåmååråstå oletetaan olevan saatavilla kevåttalvella. Puussa kasvavien jåkålien kysyntå lasketaan periaatteessa samalla tavoin kuin maassa kasvavien jåkålien ky-syntå, paitsi ettå vuorokausien måårå vuodessa on pienempi, koska puussa kasvavavien jåkålien katsotaan på-åasiassa olevan håtåravintoa. Tulokset ovat epåvarmoja kahdesta pååsyystå. Osittain niiden tekijoiden vuoksi, jotka eivåt sisålly malliin, osittain niiden tekijoiden epåtarkkuudesta, jotka sisåltyvåt malliin. Malli sisåltåå selviå todellisten yhteyksien yksinkertaistamisia. Nåmå yksinkertaistamiset johtuvat pååasiassa perustietojen puutteesta. Esimerkkinå voidaan mainita, ettå metsån tila muuttuu paljolti prognoosikauden aikana. Tåtå vaihtelua esimerkiksi puus-tossa ei kuitenkaan mallissa huomioida. Esimerkki niiden tekijoiden epåtarkkuudesta, jotka sisåltyvåt malliin, on jåkålålaidunten kasvuprosentti. Toinen esimerkki on jåkålåmåårien arviot, jotka tåsså perustuvat tutkielmiin (Eriksson, julkaisematon), joilla on ollut toinen tarkoitusperå kuin tåsså tutkimuksessa kåsiteltåvien lååninosien laiduntamahdollisuuksien arvioiminen. Mahdollisuudet varmojen johtopååtosten tekoon lisååntyvåt yhdesså parempien perustietojen myotå kåytetyistå yhteyksistå ja tiedoista. Maantieteellinen jako lååninosiin johtuu valtakunnanmetsånarvioinin rakenteesta. Olosuhteet voivat tie-tysti vaihdella nåiden lååninosien sisållå, joista jokainen sisåltåå useamman paliskunnan. Tuloksia ei siis saa tulkita paliskunta kohtaisesti. Tutkielma esittåå tavan valoittaa kuinka porohoidon jåkålålaitumet kehittyvåt suhteessa puuntuotantoon. Tulokset ovat kuitenkin liian epåvarmoja, jotta niistå voitaisiin vetåå varmoja loppupååtelmiå. Tulokset viittaavat kuitenkin, ettå tietyillå alueilla on jo talla hetkellå pula jåkålålaitumista niillå poromåårillå, joilla tassa tutkielmassa on laskettu. Laskelmat viittaavat, ettå tuotanto våhenee tulevaisuudessa, minkå pitåisi motivoida laajempaa tutkimukseen tållå alueella. Jos tulokset tåsså tutkimuksessa ovat oikeat ja jos puuntuotannollinen metsåtalous kehittyy esimerkin mu-kaisesti, pitåå poronomistajien jatkaa tai lisåtå tukiruokintaa ja/tai våhentåå porojen lukumååråå huomatta-vasti. He joutuvat my os hyodyntåmåån kaikki laiduntamiskelpoiset alueet, my os sellaiset jotka tållå hetkellå ovat våhemmån tårkeitå. Toinen tapa par ant aa tasapainoa on sopeuttaa jåkålåalueiden puuntuotannollinen metsåtalous suuremmassa måårin kuin tåsså analysoitavassa vaihtoehdossa tehdåån.